Dose-dependent effects of testosterone on proteins related to nitric oxide signaling pathway and trophic factors in the spinal cord of adolescent trained rats - Katarzyna Nierwińska; Katarzyna Nierwińska; Konstancja Grabowska; Małgorzata Chalimoniuk; Sławomir Jagsz; Józef Langfort; Andrzej Małecki; Marta Nowacka-Chmielewska (Frontiers in Sports and Active Living)
IntroductionEndurance training plays an important role in, for example, triathlon, marathon, or road cycling and in combination with strength training. Adolescence has been associated with increased interest among of young people, especially boys, in strength-related and endurance sports or body-building. Anabolic androgen steroid use is a public health threat. The present study aimed to estimate the effect of endurance training, two doses of testosterone, and the combination of these stimuli on the level and activity of proteins related to the nitric oxide (NO) signaling pathways in the spinal cord in adolescent male rats.MethodsAdult male Wistar rats were trained using a motor-driven treadmill for 6 weeks (40–60 min, 5 times per week) and/or were treated for 6 weeks with two doses of testosterone (i.m.; 8 mg/kg or 80 mg/kg body weight). At the end of the experiment, spinal cord samples were collected for further evaluation.Results and DiscussionMajor findings from the study are that a high dose of testosterone increases proteins related to the NO signaling pathway (eNOS, nNOS, CGβ1, PKC), but decreases trophic factors (BDNF, VEGF) and p-Akt. Endurance training by itself increases the spinal protein levels of CGβ1, VEGF, and kinases -p-Akt and PKC, but decreases kinase p-p38 MAPK; and the combination of endurance training and high doses of testosterone enhances changes in the protein level of nNOS, p-p38 and p-Akt. In conclusion, at least some of the effects of endurance training and testosterone may be related to the intensity of NO-related signal transmission and protein kinase systems.